Sarcopenia and it’s influencing factors among adults with asthma, chronic obstructive pulmonary disease, and tuberculosis in Penang, Malaysia - Radhiyatul Akma Mohamad Zani; Hazwani Ahmad Yusof; Nurul ‘Ain Azizan; Irfhan Ali Hyder Ali; Suhaila Ismail; Noorsuzana Mohd Shariff (BMC Public Health)
Abstract Background Chronic respiratory diseases like asthma, chronic obstructive pulmonary disease (COPD), and tuberculosis (TB) are increasing globally, leading to systemic symptoms like skeletal muscle dysfunction. Ageing and physical inactivity exacerbate sarcopenia, reducing functional capacity, disability, and quality of life. However, limited research exists on the prevalence of sarcopenia among chronic respiratory diseases in low-middle-income countries like Malaysia. Hence, this study aims to investigate the prevalence of sarcopenia and its associated risk factors among adults with asthma, COPD, and TB in Penang, Malaysia. Methods A cross-sectional study was conducted from June 2023 to March 2024. This study included 469 patients (mean age: 52.62 ± 16.61 years) diagnosed with asthma (n = 180), COPD (n = 186), or TB (n = 103) receiving treatment in chest clinics of two governmental hospitals in Penang. The SARC-F and SARC-CalF questionnaires were used to assess the participants’ risk of sarcopenia. Sarcopenia was identified using the 2019 criteria of the Asian Working Group for Sarcopenia (AWGS). The risk factors for sarcopenia in asthma, COPD, and TB patients were investigated using multivariable logistic regression. Results The prevalence of sarcopenia was 18.9% (95% CI 13.5–25.4) in patients with asthma, 33.9% (95% CI 27.1–41.2) in those with TB, and 35.9% (95% CI 26.7–46.0) in those with COPD, according to AWGS 2019 criteria. The SARC-CalF screening tool showed that 27.3% of participants had a positive risk of having sarcopenia. The independent risk factors associated with sarcopenia in asthma patients were age, physical activity and body mass index (BMI). For TB patients, significant risk factors included Chinese and other ethnicities, foreigners, lower daily protein intake, and BMI. In COPD patients, independent risk factors included age, moderate physical activity, BMI and history of heart failure. Conclusion This study highlighted a significant burden of sarcopenia among patients with asthma, COPD and TB. Non-clinical interventions such as lifestyle modification and nutritional support to the patients are crucial to maintain muscle strength and delay the onset of sarcopenia, particularly in people with chronic respiratory diseases.